Rethinking, reinterpreting and restructuring composite cities - Saǧlamer, Gülsün (Cambridge Scholars Publishing, 2017)
Developments in science and technology, demand-driven education and practices, climate change, the gradual decrease in natural resources, and economic constraints all combine to drive increased interest in research in architecture and urbanism at EU levels. In light of this, the EURAU conferences were initiated in 2004 to create a platform for researchers to share their own research outputs and knowledge, and to discuss problems emerging in architecture and urbanism with a view to develop solutions. This book brings together 19 selected papers delivered at the EURAU2014 Istanbul "Composite Citi